Prescription Pattern and Evaluation of Polypharmacy among Geriatric Outpatients: A Cross-Sectional Study - Khadka, Anjan; Kaundinnyayana, Sammodavardhana; Thakali, Kabir; Sainthwar, Siddhant Singh; Khadka, Sachita; Sharma, Surya Raj (Med Phoenix, 2025)
Introduction: Geriatric patients may present with multiple disorders, necessitating complex drug regimens that increase the risk of poly-pharmacy and associated adverse outcomes. This study aimed to evaluate prescribing patterns and assess the prevalence of polypharmacy among elderly patients attending the Family and Veteran Outpatient Department of a tertiary level hospital of Nepal, a lower middle income country. Materials and methods: A cross-sectional study was conducted from February 2024 to January 2025 (12 months), involving 200 patients aged 60 years and above after getting approval from Institutional Review Committee. Data were collected using a structured proforma, capturing demographic details and prescription information. Prescribing patterns were analyzed using the World Health Organization core prescribing indicators. Prevalence of polypharmacy and the factors associated with polypharmacy was determined. Results: The study included 200 elderly outpatients (mean age 73.16±4.56 years) and found average of 3.42 drugs per prescription, with polypharmacy (use of five or more drugs at a time)—affecting 19% of patients. Acute conditions had greater prevalence of polypharmacy than chronic conditions (55% vs. 15%), however there was no association between polypharmacy and age or gender. Patients having polypharmacy had higher levels of satisfaction (63.2% vs. 42.0%). Amlodipine, Metformin, and Losartan were three most frequently prescribed drugs. Conclusion: This study revealed 19% polypharmacy prevalence among elderly outpatients, significantly associated with acute rather than chronic conditions, with affected patients showing higher treatment satisfaction. The finding underscore the need for improved prescribing practices, with good adherence to guidelines and optimization of medicines in elderly.